Perilaku Kesehatan Anak Sekolah Dasar Memiliki Kerentanan Terjadinya Demam Berdarah Dengue - I Nyoman Ribek; Kadek Mega Asrini; Ni Luh Kompyang Sulisnadewi; I Ketut Labir (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2021)
The background of this research is because dengue fever caused by the denguevirus through the bite of the female Aedes aegypti mosquito still has a high morbidity and mortality rate, especially in elementary school children.It's not clear why elementary school-aged children have high dengue fever rates, in terms of good parental knowledge research results. This study aims to determine whether the health behavior of elementary school children has a relationship with the incidence of dengue hemorrhagic fever. This research is an analytic study with a cross sectional approach with a total sample of 62 people located at the State Elementary School 6 Banyuning Buleleng. How to take samples with simple random sampling technique. The results of the study using the Spearman rank correlation test showed an r value of -0.515 and a p value of 0.000 (α = 0.05). It was concluded that there was a significant relationship between health behavior and the incidence of Dengue Hemorrhagic Fever. It is hoped that teachers, students and parents will play an active role in eradicating dengue fever through draining, closing and burying movements.